Setting an Optimization Problem of Distributing Traffic Across Multiple Independent Paths - Alhihi, Mohammad (Discoveries in Agriculture and Food Sciences, 2017)
There appeared a need for developing a communication network for urgent need, which became world demand. The given article addresses at the solution of the problem of traffic engineering, using the mechanisms of multi-path routing within the developed algorithm, the optimal number of paths was defined. The proposed algorithm includes a multicriteria optimization procedure. The values of the maximum flow and multi-path delay are used as partial criteria. If necessary, a set of particular criteria can be extended. This allows to solve the problem of ensuring the required quality of service.